Handbook of digital and multimedia forensic evidence - Barbara, John J. (Humana Press, 2008)
The analog and digital world / Donald Justin Price -- Training and education in digital evidence / Philip Craiger -- Certification and accreditation overview / John J. Barbara -- History, concepts, and technology of networks and their security / Rebecca Gurley Bace -- The digital crime scene / Mark M. Pollitt -- Investigating cybercrime / Philippe Dubord -- Duties, support functions, and competencies: digital forensics investigators / Larry R. Leibrock -- Electronic evidence and digital forensics testimony in court / Fred Chris Smith and Erin E. Kenneally